LGBT* People in Later Life: The State of Research and Opportunities for Empirical Quantitative Analysis with Secondary Data in Germany - Lisa de Vries; Zaza Zindel; Ralf Lottmann (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2025)
Increasing population ageing and demographic change are accompanied by greater diversity among later age cohorts. This phenomenon is evident with regard to the specific aspect of sexual and gender diversity. In recent decades, an increasing number of lesbian, gay, bisexual, trans*, and other sexual and gender minority (LGBT*) people who have lived through periods with different levels of social acceptance and legal equality have been entering later life. However, little is known about the life situations of older LGBT* people in Germany, and this raises questions about how sexual orientation and gender identity affect life situations in old age in our society. Based on the life course approach and the concept of structural stigma, we first theoretically derive the consequences of historical persecution and stigmatisation for life in old age. We then analyse the current state of research on LGBT* people in later life. Due to the lack of quantitative studies on older German LGBT* people, this article mainly summarises the international state of research on differences between LGBT* and cis-heterosexual people, as well as on the ways that LGBT* people differ according to minority status and age cohort. Building on this, we provide an overview of available quantitative secondary datasets that can be used to analyse the life situations of older LGBT* people in Germany. In doing so, we discuss the potential of the study selection for analysing the relevant topics, and we conclude by discussing its limitations together with improvements that could be made to gain better knowledge about this field of research. – – Die zunehmende Alterung der Bevölkerung und der demografische Wandel gehen mit einer größeren Vielfalt in den späteren Alterskohorten einher. Dies gilt auch für den Aspekt der sexuellen und geschlechtlichen Vielfalt. Immer mehr lesbische, schwule, bisexuelle, trans* und andere Menschen aus sexuellen und geschlechtlichen Minderheiten (LGBT*) erreichen ein höheres Lebensalter und haben in den letzten Jahrzehnten unterschiedliche Phasen gesellschaftlicher Akzeptanz und rechtlicher Gleichstellung erlebt und mitgestaltet. Allerdings ist wenig über die Lebenssituation älterer LGBT*-Menschen in Deutschland bekannt und es stellt sich die Frage, wie sich sexuelle Orientierung und Geschlechtsidentität in unserer Gesellschaft auf die Lebenssituation im Alter auswirken. Auf der Grundlage des Lebenslaufansatzes und des strukturellen Stigmas leiten wir zunächst theoretisch die Folgen der historischen Verfolgung und Stigmatisierung für das Leben im Alter ab. Anschließend analysieren wir den aktuellen Stand der Forschung zu LGBT*-Personen im Alter. Aufgrund des Mangels an quantitativen Studien zu der Zielgruppe in Deutschland fasst dieser Artikel hauptsächlich den internationalen Forschungsstand zusammen, der sich mit Unterschieden zu cis-heterosexuellen Menschen, aber auch mit Unterschieden zwischen Menschen mit verschiedenen Minderheitenstatus und zwischen Alterskohorten beschäftigt. Darauf aufbauend geben wir einen Überblick über verfügbare quantitative Sekundärdatensätze, die zur Analyse der Lebenssituation älterer LGBT*-Menschen in Deutschland genutzt werden können. Dabei diskutieren wir das Potenzial der Studienauswahl für die Analyse relevanter Themen und erörtern abschließend Einschränkungen und mögliche Verbesserungen, um Erkenntnisse in diesem Forschungsfeld zu gewinnen.
Keywords: 300; Sexual and gender identity; Social inequality; Health disparities; Data infrastructure; Later adulthood; Sexuelle und geschlechtliche Identität; Soziale Ungleichheit; Gesundheitliche Ungleichheit; Dateninfrastruktur; Späteres Erwachsenenalter